Is China's interest for the Arctic driven by Arctic shipping potential? - Huang, Linyan; Alexeeva, Olga V.; Lasserre, Frédéric (Asian Geographer, 2016)
Interest from the Chinese government has been on the rise since about 2005, and the media have widely reported on these Chinese projects. China is often described as being very interested in both Arctic mineral resources and the opening of Arctic shipping routes, but in this characterization there is a hint of a perceived threat, as commentators are often stressing out that China’s appetite may lead Beijing into considering the Northwest Passage an international strait and resources as open up for grabs. However, the motives for this Chinese interest boils down to three points: diplomacy, access to natural resources and access to Arctic sea routes. To what extent are Chinese shipping firms really interested in developing active service along these polar waterways?